The Aging Slopes of Brain Structures Vary by Ethnicity and Sex: Evidence From a Large Magnetic Resonance Imaging Dataset From a Single Scanner of Cognitively Healthy Elderly People in Korea - Choi, Yu Yong; Lee, Jang Jae; Choi, Kyu Yeong; Seo, Eun Hyun; Choo, IL Han; Kim, Hoowon; Song, Min-Kyung; Choi, Seong-Min; Cho, Soo Hyun; Kim, Byeong C.; Lee, Kun Ho; , for the Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Aging Neuroscience, 2020)
The aging of brain is a well-investigated topic, but existing analyses have mainly focused on Caucasian samples. To investigate brain aging in East Asians, we measured cortical and subcortical volumes from MRI scans of 1,008 cognitively normal elderly Koreans from the Gwangju Alzheimer’s and Related Dementia cohort, and 342 Caucasians from the Alzheimer ’s Disease Neuroimaging Initiative database. To determine whether the aging effect varies with ethnicity and sex, beta coefficients of age and the confidence intervals were estimated in each ethnicity-sex group using a bootstrap method and a regression analysis using the relative volume to intracranial volume as predicted. The betas or aging slopes largely were not significantly different between ethnicity-sex groups in most types of brain structures. However, ethnic differences between the two female groups were found in the brain, most cortical regions and a few subcortical regions. Ethnic differences in brain aging are likely due in large part to genetic factors, so we compared carriers and non-carriers of a gene relevant to longevity and neurodegenerative diseases like apolipoprotein E (APOE) ε4. The regions with ethnic differences in women also showed significant differences between Korean APOE ε4 non-carriers and Caucasian APOE ε4 carriers. Furthermore, Caucasian women showed significant APOE ε4 effects in the largest number of regions. These results illustrates that much of the ethnic differences in females may be explained by synergistic effects of ethnic background and APOE ε4 carrier status. Our results suggest that sex-dependent differences of aging between ethnic backgrounds may be due to ethnicity-dependent effects of genetic risk factors such as APOE ε4. We also presented the normative information on volume estimates of the brain structures of the elderly Korean people in the subdivided age groups. This normative information of the aging brain stratified by ethnicity provides the age-related reference ranges quantified to replace visual judgement and facilitate precise clinical decision making.